Understanding the Nitty-Gritty of Up-to-Date of Pakistan’s Customs Act, 1969 - Naveed-ul-Haq (Frontiers in Law, 2023)
Pakistan’s Customs Act, 1969 was enacted consolidating and amending the various laws on Customs. There are mainly six methods of valuation of goods including transaction value method, identical goods method, similar goods method, deductive methods, computed method and fall back method. Under Section 79 of the Act, Goods Declaration is filed duly supported by various documents for assessment of leviable duty and taxes. In case of misdeclaration, untrue statement or error etc. section 32 comes into play. Search Warrant is to be obtained by the Gazetted Officer of Customs from the Judicial Magistrate to recover the secreted goods under Section 162 of the Act, Seizure of things liable to confiscation is made under Section 168 of the Act. Section 156 provides the scope of offence(s), nature of breach and penalty thereof. Section 187 of the Act fixes initial burden of proof upon the person involved, which may be rebutted by the Customs authorities. The purpose of adjudication includes confiscation of goods, recovery of duty and other taxes not levied or short levied, recovery of erroneously refunded amount and imposition of fine. An option to fine in lieu of confiscation of goods can be given under Section 181 of the Act. The pecuniary power of adjudication is provided under Section 179 of the Act, whereas there are Appellate forums available in the form of Collector Appeals, Customs Appellate Tribunal and High Court. In addition to this, another mechanism under Alternate Dispute Resolution (ADR) is available under Section 195-C of the Act. In case of commission of cognizable offence, a FIR is lodged and a Special Judge takes cognizance of the offence(s) under the Code of Criminal Procedure, 1989. An appeal or Revision can be filed before the Court having the Powers High Court. The main challenge before the Customs is determination of value of goods paid or payable in relation to the item being valued. In case inaccurate value, either it is the business class who suffers or the state’s fiscal interests are jeopardized on account of lack of requisite capacity of the Customs Officer to successfully address the issue of value of goods and pass the buck onto the importer for charging misdeclaration and a lengthy process of adjudication is initiated against the importer and exporter as well as Clearing Agent as this value holds good for the imposition of Sales Tax, Income Tax and Federal Excise duty.